Effect of divided nitrogen and sulfur fertilization on the quality of winter wheat - Diósi, Gerda; Sipos, Péter (Acta Agraria Debreceniensis, 2016)
The ecological characteristics and agro-ecological conditions in Hungary provide opportunities for quality wheat production. For the successful wheat production besides the favorable conditions; the proper use of expertise and appropriate cultivation techniques are not negligible. Successful cultivation affected by many factors. To some extent we can affect, influence and convert the abiotic factors. Today, a particularly topical issue is the question of nutrition and that the species’ genetic code can be validated using the appropriate quantity and quality fertilizer. Beyond determining the fertilizer requirements of the winter wheat it is important to align the nutrient to the plant’s nutrient uptake dynamics and to ensure its shared dispensing. In any case, it is important to note the use of autumnal base-fertilizer as complex fertilizer. Hereafter sharing the fertilizer during the growing season with the recommended adequate nitrogen dose.The first top dressing of winter wheat in early spring (the time of tillering) can be made, the second top dressing at the time of stem elongation, and the third top dressing at the end of the blooming can be justified. Determining the rate of fertilizer application depends on the habitat conditions and the specific nutrient needs of plants. In autumn the 1/3 of the planned amount of basic fertilizer should be dispensed (in case of N). During setting our experiment we used 3 doses (0 kg ha-1 N-1 active ingredient; 90 kg ha-1 N-1 active ingredients and 150 kg ha-1 N-1 active ingredient). Application dates beyond the autumn basic fertilization are the following: in one pass in early spring, divided in early spring and the time of run up, early spring and late flowering. In addition to nitrogen the replacement of sulfur gets a prominent role as a result of decreased atmospheric inputs. The proper sulfur supply mainly affects the quality parameters. It influences positively the wheat flour’s measure of value characteristics (gluten properties, volume of bread, dough rheology. In terms of nitrogen doses; the larger amounts (150 kg ha-1 N-1 drug), is the proposed distributed application, while in the case of lower nitrogen (90 kg ha-1 N-1 drug) in a single pass in the early spring can achieve better results. After using sulfur the quality values among the nutritional parameters that can be associated with gluten properties took up higher values than the samples not treated with sulfur.